The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/978-3-540-87991-6_26
|View full text |Cite
|
Sign up to set email alerts
|

A General-Purpose Context Modeling Architecture for Adaptive Mobile Services

Abstract: Abstract. Mobile context-aware computing aims at providing services that are optimally adapted to the situation in which a given human actor is. An open problem is that not all mobile services need contextual information at the same level of abstraction, or care for all aspects of the user's situation. It is therefore impossible to create a unique context model that is useful and valid for all possible mobile services. In this paper we present a compromise: a three-tiered context modeling architecture that off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In a recent work on mobile services by Pederson et al (2008) we have found many interesting similarities with our approach, especially in the context model. One of their first statements is that different applications cater for different aspects of the user's context, which means that a unique context model for different applications is not a viable solution.…”
Section: Related Workmentioning
confidence: 67%
“…In a recent work on mobile services by Pederson et al (2008) we have found many interesting similarities with our approach, especially in the context model. One of their first statements is that different applications cater for different aspects of the user's context, which means that a unique context model for different applications is not a viable solution.…”
Section: Related Workmentioning
confidence: 67%
“…In a recent work on mobile services by Pederson et al (2008), we have found many interesting points that we share in our approach. One of their first statements is that different applications cater for different aspects of the user's context, which means that a unique context model for different applications is not a viable solution.…”
Section: Introductionmentioning
confidence: 90%
“…Vazquez 50 presents a framework for intelligent and global context‐awareness, and serendipitous collaboration even with remote objects and services. In 51 Pederson et al present a three‐tiered context‐modeling architecture in which lower level, medium‐level, and higher level context models are distinguished. In addition, Aura 52 is an architectural system for ubiquitous computing with a special focus on context awareness, including context switching based on user mobility.…”
Section: Background Literature and Contributionsmentioning
confidence: 99%